Restorative Justice in Juvenile Courts in Brazil: a brief review of Porto Alegre and São Caetano pilot projects - Achutti, Daniel; Centro Universitário La Salle – Canoas (2012)
In this paper, it is presented the results of the first three years (2005-2007) of the application of Restorative Justice (RJ) in the Brazilian juvenile justice system. To this end, it was made a bibliographical and documental researches, so all data used in the paper has not been collected directly by the authors. Good results are verified, despite the almost complete absence of publicity given to the work developed in the country. It was also noticed a considerable lack of dialogue between those who are responsible for the programmes, the legal actors involved, and the local Universities. For even better results, it is suggested that all institutions involved improve the dialogue between them and encourage scientific researches of their own practices.